Single-acetylene linked porphyrin nanorings - Rickhaus, M; Vargas Jentzsch, A; Tejerina, L; Gruebner, I; Jirasek, M; Claridge, T; Anderson, H (American Chemical Society, 2017)
The synthesis of ethyne-linked porphyrin nanorings has been achieved by template-directed Sonogashira coupling. The cyclic hexamer and octamer are predicted by DFT to adopt low symmetry conformations, due to dihedral twists between neighboring porphyrin units, but their symmetries are effectively D6h and D8h, respectively, in solution by 1H NMR. The fluorescence spectra indicate that the singlet excited states of these nanorings are highly delocalized.